Overview of Evidence-Based Chemotherapy for Oral Cancer: Focus on Drug Resistance Related to the Epithelial-Mesenchymal Transition - Jingjing Sha; Yunpeng Bai; Huy Xuan Ngo; Tatsuo Okui; Takahiro Kanno (Biomolecules, 2021)
The increasing incidence of resistance to chemotherapeutic agents has become a major issue in the treatment of oral cancer (OC). Epithelial-mesenchymal transition (EMT) has attracted a great deal of attention in recent years with regard to its relation to the mechanism of chemotherapy drug resistance. EMT-activating transcription factors (EMT-ATFs), such as Snail, TWIST, and ZEB, can activate several different molecular pathways, e.g., PI3K/AKT, NF-κB, and TGF-β. In contrast, the activated oncological signal pathways provide reciprocal feedback that affects the expression of EMT-ATFs, resulting in a peritumoral extracellular environment conducive to cancer cell survival and evasion of the immune system, leading to resistance to multiple chemotherapeutic agents. We present an overview of evidence-based chemotherapy for OC treatment based on the National Comprehensive Cancer Network (NCCN) Chemotherapy Order Templates. We focus on the molecular pathways involved in drug resistance related to the EMT and highlight the signal pathways and transcription factors that may be important for EMT-regulated drug resistance. Rapid progress in antitumor regimens, together with the application of powerful techniques such as high-throughput screening and microRNA technology, will facilitate the development of therapeutic strategies to augment chemotherapy.